A Diagnostic Supportive Sign for the Cause of Death Diagonal Ear Lobe Crease - Demirel, Birol; Bahçecioğlu, Meltem; Akar, Taner; Şenol, Ender (The Bulletin of Legal Medicine, 2005)
Coronary artery disease is a major cause of natural death. The high incidence and mortality of these diseases arised a need to investigate possible risk factors beyond well known. Diagonal ear lobe crease (DEC), was the physical sign, described in 1973. We investigated the possibility of DEC as a helpful predictive sign in the postmortem examination of forensic sudden death cases. The angiographic results revealed that whenever the percentages of the stenosis in left descending coronary artery, circumflex artery and right coronary artery increased, the incidence of the DEC did so accordingly. These results were correlated with the previous studies reporting significant correlation between coronary artery disease and the DEC. Particularly, in the absence of supportive medical history and without a physical sign of trauma, the presence of DEC could well be a supportive sign for the physician to consider the coronary artery disease as a cause of death. Key words: Diagonal ear lobe crease, coronary artery disease, death investigation